Periodontal disease and oral health‐related behavior as factors associated with preterm birth: a case–control study in south‐eastern Brazil. (16th August 2013) - Macedo, J. F.; Ribeiro, R. A.; Machado, F. C.; Assis, N. M. S. P.; Alves, R. T.; Oliveira, A. S.; Ribeiro, L. C.
<x xml:space="preserve">Abstract</x> Background and Objective Several studies have suggested a link between periodontal disease and preterm birth, but the mechanism of how this occurs remains controversial. Therefore, this study aimed to investigate whether periodontal disease, defined according to two commonly used clinical definitions, is associated with preterm birth and to examine the association regarding oral health‐related behaviors during pregnancy. Material and Methods This case–control study included women 18–40 years of age. Demographic and socio‐economic data, information on current and previous pregnancies, and data on dental health‐related behaviors and periodontal clinical parameters were collected within 48 h postpartum. Periodontal disease was assessed according to two definitions: four or more teeth with at least one site showing a probing depth of ≥ 4 mm and clinical attachment level of ≥ 3 mm (Definition 1); or at least one site with probing depth and clinical attachment level of ≥ 4 mm (Definition 2). The chi‐square test was used to examine differences in the proportion of categorical variables. Bivariate analysis was performed to analyze the proportion of preterm births with respect to independent variables. Multiple logistic regression analyses were used to assess the association between periodontal disease and preterm birth. Odds ratios (ORs) were calculated with a 95% confidence interval (95% CI). Results A total of 296 postpartum women met the inclusion criteria. The case group included 74 women who delivered a preterm neonate (< 37 wk of gestation) and the control group included 222 women with deliveries at term (≥ 37 wk). Periodontal disease according to Definition 1 was not associated with fewer weeks of gestation (adjusted OR (ORadjusted) = 1.62; 95% CI = 0.80–3.29; p = 0.178). However, a significant association was found between periodontal disease, according to Definition 2, and preterm birth (ORadjusted = 1.98; 95% CI = 1.14–3.43; p = 0.015). Increased appetite and a low number of daily toothbrushings were associated with preterm birth, regardless of the definition of periodontal disease used. Conclusion Periodontal disease defined according to Definition 2 and unfavorable oral health‐related behavior were factors associated with preterm birth.